Physicochemical preservation of blueberries treated with chitosan and salicylic acid in postharvest - Ramos-Bell, Surelys; Diaz-Cayetano, Gerónimo; Hernández-Montiel, Luis Guillermo; Velázquez-Estrada, Rita María; Montalvo-González, Efigenia; Gutiérrez-Martínez, Porfirio (Revista Mexicana de Ciencias Agrícolas, 2024)
The blueberry (Vaccinium corymbosum L.) fruit is characterized by its antioxidant properties due to its content of phenolic compounds, anthocyanins, and other compounds. However, it is susceptible to deterioration, loss of its quality and shelf life. In order to preserve its physicochemical properties and quality, the use of the combined treatment of chitosan and salicylic acid is proposed as the main objective. The research was carried out during 2022, in which the preservation of blueberry fruits in the postharvest stage was evaluated through the application of a combined treatment of chitosan and salicylic acid. The evaluation of the quality parameters showed that the application of the combined treatment maintained the firmness of the fruits for longer and reduced physiological weight loss by up to 11%. Changes in blueberry total soluble solids, pH, titratable acidity, and color were delayed for more days, but postharvest fruit quality was maintained. The respiration rate of the blueberries decreased by the application of chitosan plus salicylic acid and there was an induction of the phenylalanine ammonia lyase enzyme during the first 24 h of storage of the blueberries due to the effect of chitosan combined with salicylic acid. Through this research, it was concluded that chitosan and salicylic acid as a combined treatment can be a sustainable alternative to the use of fungicides to preserve blueberry fruits in the postharvest stage.